Răspuns :
[tex]\it log_3(x-1)=log_3(6-x)-2 \Rightarrow log_3(6-x)-log_3 (x-1)=2 \Rightarrow \\ \\ \\ \Rightarrow \log_3\dfrac{6-x}{x-1}=2 \Rightarrow \dfrac{6-x}{x-1}=3^2 \Rightarrow \dfrac{6-x}{x-1}=9 \Rightarrow \dfrac{6-x}{x-1}\ \ -\ \ ^{x-1)}9=0 \Rightarrow\\ \\ \\ \Rightarrow\dfrac{6-x-9x+9}{x-1}=0 \Rightarrow \dfrac{15-10x}{x-1}=0 \Rightarrow 15-10x=0|_{:10} \Rightarrow\\ \\ \\ \Rightarrow 1,5-x=0 \Rightarrow x=1,5[/tex]
Observație:
Verificarea este obligatorie, pentru că am evitat să căutăm
condițiile de existență. Uneori e mai rapid așa.